Reproducing Animals in Latin America - Soluri, John (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2024)
This article explores the history of artificial insemination (AI) in order to suggest the value of writing histories of human intervention in animal reproduction in Latin America/Caribbean. Writing histories of how people have tried to direct animal reproduction is important for understanding changes in biological diversity and also for exploring intimate relations between people and animals beyond killing. Stories of human attempts to inseminate animals have circulated for centuries, but institutional programs emerged at the end of the nineteenth century and expanded greatly in the mid-twentieth century. After an early focus on horses, practitioners of AI shifted to livestock including dairy cows and sheep. In Latin America, as elsewhere, livestock owners and government agencies viewed AI as a means to boost yields of food and fibers via the efficient transfer of desirable genetic traits across generations of livestock. The extraction and storage of semen enabled ranchers to inseminate female livestock with sperm from “pedigree” bulls or rams that they did not own or that were even deceased. The diffusion of AI relied on inexpensive technologies and new forms of cooperation and communication between people and animals. In the late twentieth century, conservation biologists turned to AI as a means to reproduce captive populations of endangered or threatened species. The history of AI therefore allows us to cross the dividing line between “domesticated” and “wild” animals.